2008
DOI: 10.4321/s1130-01082008001100010
|View full text |Cite
|
Sign up to set email alerts
|

Toxicidad hepática recurrente secundaria a metilprednisolona intravenosa

Abstract: INTRODUCCIÓNLa hepatotoxicidad inducida por fármacos es una de las etiologías más comunes de hepatitis aguda en nuestro medio y representa la causa más frecuente de fallo hepático fulminante en EE. UU. (1). Sin embargo, las tasas reales de hepatitis secundaria a fármacos son desconocidas (2). La expresión clínica de estos cuadros es muy variable, oscilando entre alteraciones asintomáticas de las enzimas hepáticas hasta fallo hepático agudo fulminante y su diagnóstico precisa de un alto índice de sospecha y se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 23 publications
0
4
0
2
Order By: Relevance
“…However, acute liver failure is rare, and up to 17% of cases are attributed to idiosyncratic reactions, determined by individual susceptibility and not related to the dose of the drug. There are no models for predicting adverse reactions [9,11]. …”
Section: Discussionmentioning
confidence: 99%
“…However, acute liver failure is rare, and up to 17% of cases are attributed to idiosyncratic reactions, determined by individual susceptibility and not related to the dose of the drug. There are no models for predicting adverse reactions [9,11]. …”
Section: Discussionmentioning
confidence: 99%
“…To our concern, a limited number of cases of IVMP‐induced hepatotoxicity in MS patients have been reported . In patients at risk, there has been proposed a strict monitoring of liver function once a week during pulse therapy, and once a month for the subsequent 12 months .…”
Section: Discussionmentioning
confidence: 99%
“…In vivo liver histopathology was performed in only 8 cases, showing a large spectrum of lesions. Fernandez et al reported recurrent acute hepatitis that was characterized by necrosis on histopathological examination, related to intravenous MT that was given on 3 occasions for the management of relapsing multiple sclerosis [4]. Loraschi et al reported 2 cases of liver damage that was related to high-dose MT therapy for demyelinating disease [5].…”
Section: Discussionmentioning
confidence: 99%